Notice to submit financial proposal as a single source for the procurement of goods, works and services mentioned in this letter - Brac University (Brac University, 2023)
This record consists of general correspondence regarding the notice to submit financial proposal as a single source for the procurement of goods, works and services mentioned in this letter of BRACU new campus project site.